A Review on Industrial Banana Production in Cambodia - Thorn Navy; Serey Mardy (International Journal of Sustainable Applied Sciences, 2023)
The most common banana cultivars grown in Cambodia are Namva, Pong Mone, Ambong Meas, Ambong Kheiv, Ambong Loeug, and Slabmuk. Cambodia bananas were exported to China for the first time, becoming the first Cambodian fruit shipped to China. The Ministry of Agriculture, Forestry, and Fisheries of Cambodia reports that in the first half of 2022, the country exported 218,000 tons of fresh bananas, all of which were sold to China. Fresh bananas have emerged as Cambodia's greatest agricultural export, with an expected yearly export amounting to 500,000 tons. This review paper's goal is to compile the literature on banana production in Cambodia. Growing and taking care of the banana plant is simple. However, it also has some diseases and insects that harm its leaves and stems. The most prevalent diseases that may cause issues during the wet season are circular, depressed areas, and dry reddish brown. Banana growers should focus on standardization, technologies suitable for various cultivation systems, high-yield variety selection, planting healthy, disease-free, planting material, selecting the proper planting density, timely and need-based input application, and irrigation water should be the main priorities for banana growers, and to bridge the gap between yield and potential yield per unit area nutrients, weed control, etc., are important.